Patient Perspectives and Experiences of Low Back Pain Care Pathways in Primary Care - Boyle, Eileen (Curtin University, 2022)
Four studies explored patient perspectives and experiences of LBP care pathways and acceptance and reported outcomes of a concurrent novel stratified care pathway in Australian primary care. People with low back pain want to be heard and prefer care that is responsive to their individual needs. Care pathways within a dominant biomedical approach are ineffective when pain persists, and current pathway outcome measures may be insufficient in capturing outcomes that are meaningful to the patient.